Hidden Unemployment in Polish Industry (1945–1956) - Chumiński, Jędrzej (Studia Historiae Oeconomicae, 2024)
One of the main factors determining the weakness of the socialist economy was the phenomenon of hidden unemployment, which means excessive employment in industrial plants in relation to needs. This phenomenon should be considered in two aspects: economic and social. The aim of this article is to determine the economic and social consequences of the phenomenon of hidden unemployment in the Polish economy in the first years after the WWII. The article is based on the literature on the subject, as well as source research conducted at the Archives of New Records and the Archives of the Institute of National Remembrance in Warsaw. To analyze the socio-demographic characteristics of the staff of four industrial plants, the personal files of employees collected in the plant archives were used. The research conducted indicates that one of the main sources of weakness of the socialist economy was the situation on the labor market, and especially the phenomenon of over-employment. In the economic sphere, it meant that the dominance of an excessive number of low-skilled workers in the composition of the industrial workforce resulted in poor labor productivity, abysmal production quality, non-compliance with standards in technological processes, destruction of work ethics, poor discipline, increased personnel turnover, etc. It is a measure of the irrationality of the system that the employment of a significant proportion of these workers was not the result of either economic or social necessity, but a consequence of the erroneous economic development model adopted, based on the use of low-skilled and poorly paid labor. In social terms, however, the employment of these people meant that the communist regime could count on relatively considerable public support among them. Authoritarian, non-democratic parties (such as the PPR and PZPR), appealing to populist slogans and fomenting conflicts with other social groups corresponded in terms of their programs and modus operandi to people with high levels of authoritarian attitudes.